Influence of Production Based Training Learning Model on Student Learning Outcomes Reviewed from Entrepreneurial Interests - Hikmah, Yuniar Fitria; Nurlaela, Luthfiyah; Ismawati, Rita (International Journal for Educational and Vocational Studies, 2020)
The study aims to determine the interest of entrepreneurial students taught using Production Based Training (PBT) learning models and students taught using live learning. To learn the learning outcomes of high-entrepreneurial interests. The method used in this study was experimentation using factorial research design. The design used is 2x2 factorial design, as this design can be used to see students ' learning outcomes before they are given learning and after learning. The results of the study found that: (1) Student learning outcomes using PBT learning models are significantly higher than those using MPL;(2) Learning results of students who have a high entrepreneurial interest using PBT learning models and by using a higher MPL significantly in comparison to learning outcomes of low-entrepreneurial interests that use Model of PBT Learning and using MPL: (3) There is a significant interaction between learning models and entrepreneurial interest in student learning outcomes. The study concluded that: (1) The PBT learning model can increase the interest of entrepreneurial students; (2) Students who have a high entrepreneurial interest, higher learning outcomes than students with low entrepreneurial interest rates; and (3) there is an interaction between learning models and entrepreneurial interests in student learning outcomes.